2019
DOI: 10.14488/bjopm.2019.v16.n3.a9
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation technologies as an enabler for sustainable logistics and supply chain processes – an exploratory framework

Abstract: Goal: The aim is to present a literature review for identifying digital transformation technologies (DTT) for manufacturing and pointing out their capabilities and applications. Furthermore, the paper lays out an exploratory framework to depict the impact scope of the cases on logistics and supply chain management (L&SCM) processes. Design / Methodology / Approach: The identification of relevant DTTs and their capabilities is based on a systematic literature review. The exploratory framework builds u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…The results of this study enabled us to validate all three hypotheses previously presented. While some earlier studies highlighted the potential impact of the use of certain DSC tools on SC risk mitigation (Baryannis et al , 2019), SC traceability and transparency (Somapa et al , 2018; Junge, 2019), SC visibility and information sharing (Koonce, 2016; Kache and Seuring, 2017; Lezoche et al , 2020), the efficiency of SC processes (Junge, 2019; Zhang and Zhao, 2019) and even strategic decision making in the SC (Bienhaus and Haddud, 2018; Lezoche et al , 2020), none has ever statistically confirmed the relationship between SC digitalisation and SCR.…”
Section: Results Discussionmentioning
confidence: 99%
“…The results of this study enabled us to validate all three hypotheses previously presented. While some earlier studies highlighted the potential impact of the use of certain DSC tools on SC risk mitigation (Baryannis et al , 2019), SC traceability and transparency (Somapa et al , 2018; Junge, 2019), SC visibility and information sharing (Koonce, 2016; Kache and Seuring, 2017; Lezoche et al , 2020), the efficiency of SC processes (Junge, 2019; Zhang and Zhao, 2019) and even strategic decision making in the SC (Bienhaus and Haddud, 2018; Lezoche et al , 2020), none has ever statistically confirmed the relationship between SC digitalisation and SCR.…”
Section: Results Discussionmentioning
confidence: 99%
“…Such an economic transformation caused by the growth and development of the digital economy forces the content, methods, technical means and forms of employee training to change. In the context of sustainable competitive advantage, the needs of the digital economy enhance the role and importance of the scientific and educational sphere [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the adoption of AI technology in the shipping industry will assist in the completion of repetitive, timeconsuming processes and predictive maintenance of ships, and the loading/unloading of equipment, thereby saving labor costs, improving efficiency, and increasing revenue. Digital transformation provides customers with real-time inquiries and quotations, space booking, customs clearance, and inland delivery services, which have reduced cost and increasing productivity (Mubarak et al, 2019), improved logistics efficiency and competitiveness (Schwertner, 2017;Cichosz, 2018;Erceg and Damoska-Sekulowska, 2019;Cichosz et al, 2020), improved business models (Berman and Marshall, 2014;Schallmo et al, 2020), enhanced relationships with customers (Morakanyane et al, 2017;Nowicka, 2020;Lima and Pacheco, 2021), and led to sustainable logistics and business performance (Lambrou et al, 2019;Junge, 2019;Mubarak et al, 2019) that surpass the traditional limitations. Thus, we propose that: H4.…”
Section: Digital Transformation and Benefitsmentioning
confidence: 99%